Ultrasound assisted extraction of cellulose and nanocellulose from coconut shell / Pavitra Mohan - Pavitra , Mohan (2024)
Cellulose and nanocellulose are known for their widespread availability, biodegradability, and distinctive physical and chemical properties. Due to that, they have attracted significant interest in recent years, making them well-suited for a variety of applications. This research focuses on the extraction of cellulose and nanocellulose from coconut shell using ultrasound. This study involves two types of cellulose extraction; alkali and bleached cellulose (ABC) and ultrasound assisted extracted cellulose (UAEC). The ABC was subjected to further ultrasonication to obtain nanocellulose. During the nanocellulose extraction, two parameters - sonication power and duration, are varied to investigate their effect on the extracted nanocelluloses. The products were then characterized using attenuated total reflection- Fourier transform infrared spectroscopy (ATR-FTIR), X-Ray diffraction analysis (XRD), thermogravimetric analysis (TGA), field emission scanning electron microscope (FESEM) and transmission electron microscope (TEM). The ATR-FTIR results showed the absence of peaks attributed to lignin and hemicellulose in the ABC, UAEC and nanocellulose sample. This confirms the effective removal of these materials through the chemical treatments. FESEM analysis reveals the production of micro-sized cellulose (ABC and UAEC), whereas TEM results confirm the extraction of nanocellulose by showcasing nanometer-sized products. The size of nanocellulose sample decreases with increasing sonication power and duration. This is because as sonication power and duration increase, the collapsing cavitation bubbles generate mechanical stress on the cellulose surface, resulting in the breakdown of sample into smaller-sized components. The TGA and XRD results shows improved thermal stability and crystallinity in ABC and UAEC, attributed to the elimination of the non-cellulosic constituents. However, the thermal stability and crystallinity of nanocellulose samples are lower compared to ABC, likely due to the cavitation effect caused by sonication. Moreover, the thermal stability and crystallinity of the nanocellulose sample decrease with increasing sonication power and duration. This is attributed to the increasing collapse of cavitation bubble near the cellulose surface as sonication power and duration increase, which damages the crystalline region. These findings collectively indicate that ultrasonication stands as an efficient and promising method for the extraction of both cellulose and nanocellulose.